Possible molecular and cellular mechanisms at the basis of atmospheric electromagnetic field bioeffects - Cifra, Michal; Apollonio, Francesca; Liberti, Micaela; García-Sánchez, Tomás; Mir, Lluis M (International journal of biometeorology, 2021)
Mechanisms of how electromagnetic (EM) field acts on biological systems are governed by the same physics regardless of the origin of the EM field (technological, atmospheric...), given that EM parameters are the same. We draw from a large body of literature of bioeffects of a man-made electromagnetic field. In this paper, we performed a focused review on selected possible mechanisms of how atmospheric electromagnetic phenomena can act at the molecular and cellular level. We first briefly review the range of frequencies and field strengths for both electric and magnetic fields in the atmosphere. Then, we focused on a concise description of the current knowledge on weak electric and magnetic field bioeffects with possible molecular mechanisms at the basis of possible EM field bioeffects combined with modeling strategies to estimate reliable outcomes and speculate about the biological effects linked to lightning or pyroelectricity. Indeed, we bring pyroelectricity as a natural source of voltage gradients previously unexplored. While very different from lightning, it can result in similar bioeffects based on similar mechanisms, which can lead to close speculations on the importance of these atmospheric electric fields in the evolution.
Keywords: Electromagnetic field; Humans; Electricity; Bioeffects; elektřina; Electromagnetic Fields; Atmosphere; lidé; elektromagnetická pole